Evaluation Of Salmonella Typhi Antigens Hlye And Ynce For The Detection Of Typhoid Fever And Its Carriers - Joseph, Freddy Franklin Anthony (2019)
Salmonella Typhi (S. Typhi) is the causative agent of typhoid fever (TF) that causes millions of infections and 1% of mortality worldwide. TF is highly endemic in Southeast Asia and sub-Saharan Africa. Certain individuals with TF may not recover fully and can become carriers that do not show any symptoms of the disease. The carriers can then spread the disease when they come into contact with food and water. Antibodies against S. Typhi HlyE are elevated among patients with TF compared to healthy individuals, while antibodies against YncE were reported to be elevated among carriers of S. Typhi. Rapid and accurate methods to diagnose individuals with TF or who are carriers are crucial to manage the disease. In this study, recombinant HlyE and YncE antigens were found to be useful for the identification of individuals with TF and those who are possible carriers. Firstly, recombinant HlyE and YncE were expressed and purified. Next, rHlyE and rYncE ELISAs were developed to enable quantitative screening of many samples simultaneously to identify those with elevated IgM, IgG and IgA antibodies against the antigen. A total of 425 serum samples (acute typhoid patients, carriers, food handlers, other febrile, and healthy individuals) were screened with the ELISAs.The rHlyE-IgG, -IgA and -IgM ELISAs demonstrated a sensitivity of 70%, 80% and 11% respectively to detect acute typhoid patients, and with a combined sensitivity of 83%.The rYncE ELISA identified 16 possible carriers based on their antibody profiles. Taken together, this study showed that HlyE antigen could be used to identify individuals with TF while the YncE antigen may be used to identify possible carriers, but further validation is required.